A Synergic Effect of Bi-metallic Layered Hydro-Oxide Cocatalyst on 1-D TiO2 Driven Photoelectrochemical Water Splitting - Ali, Rana Basit; Sial, Qadeer Akbar; Lee, Young Jae; Waqas, Muhammad; Kalanur, Shankara S.; Seo, Hyungtak (Journal of Asian Ceramic Societies, 2023)
Photoelectrochemical (PEC) water splitting is one of the most sustainable approaches for converting solar energy into hydrogen fuel. Affordable and robust photoelectrodes are crucial for the commercialization of PEC technologies. Recently, transition metal-based co-catalysts, especially Ni- and Fe-based catalysts, have attracted much interest owing to their exceptional OER characteristics. Given this, we here proposed the decoration of a Fe-Ni-based cocatalyst on the surface of the TiO2 photoanode for PEC water splitting. The TiO2 photoanode was hydrothermally synthesized and then decorated by Fe-Ni hydroxide catalyst using photo-assisted electrodeposition. The optimized TiO2/FeNiOOH photoanode exhibited the maximum photocurrent density value of 1.36 mA cm−2, which is almost twice the value obtained for bare TiO2, at 1.23 V vs RHE under the AM 1.5 G illumination. Due to the enhanced light absorption in the UV region, the optimized photoanode exhibited remarkable IPCE and photoconversion efficiency of 87.8% and 0.93%, respectively. Furthermore, excellent faradaic efficiencies of ∼90% for H2 and ∼70% for O2 generations were obtained. Predominantly, the enhancement in the photocurrent potentials was explained in detail. Our study shows the roles and benefits of using bimetallic catalysts with TiO2 photoanodes for sustainable water-splitting applications.
Keywords: Bi-metallic cocatalyst; Co catalysts; H 2 production; Metallics; Photo assisted electrodeposition; Photo-anodes; Photo-assisted; Photoelectrochemical water splitting; Synergic effects; TiO2 NR; Bi-metallic cocatalyst; H2 production; PEC water splitting; Photo assisted electrodeposition; TiO2 NRs